2016
DOI: 10.1111/boj.12386
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of some leaf characteristics of Australian mangroves

Abstract: Leaf characteristics reflecting the size, lifespan (longevity), moisture content (degree of succulence) and complexity of structure of 20 mangrove species were studied over several years at 13 locations along the tropical and subtropical Australian coast. These characteristics were found to fall generally within the ranges of those for woody species from other ecosystems. With the exception of one species, it was found that leaf longevity was related inversely to leaf moisture content, increasing from nearly 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The spectrum of values of major true mangroves ranges from 4 cm 2 (Lumnitzera racemosa) to ca. 70 cm 2 for some Rhizophoraceae (Rhizophora mucronata, Rhizophora apiculata, and Rhizophora lamarckii ;Ball, 1988;Saenger and West, 2016). Interestingly, another genus of Rhizophoraceae, Ceriops, represents the lower end of the spectrum (8-12 cm 2 in Ceriops tagal : Ball, 1988;Okello, 2014; 12 cm 2 in Ceriops australis: Saenger and West, 2016).…”
Section: Leaf Area and Mass Per Areamentioning
confidence: 99%
See 3 more Smart Citations
“…The spectrum of values of major true mangroves ranges from 4 cm 2 (Lumnitzera racemosa) to ca. 70 cm 2 for some Rhizophoraceae (Rhizophora mucronata, Rhizophora apiculata, and Rhizophora lamarckii ;Ball, 1988;Saenger and West, 2016). Interestingly, another genus of Rhizophoraceae, Ceriops, represents the lower end of the spectrum (8-12 cm 2 in Ceriops tagal : Ball, 1988;Okello, 2014; 12 cm 2 in Ceriops australis: Saenger and West, 2016).…”
Section: Leaf Area and Mass Per Areamentioning
confidence: 99%
“…70 cm 2 for some Rhizophoraceae (Rhizophora mucronata, Rhizophora apiculata, and Rhizophora lamarckii ;Ball, 1988;Saenger and West, 2016). Interestingly, another genus of Rhizophoraceae, Ceriops, represents the lower end of the spectrum (8-12 cm 2 in Ceriops tagal : Ball, 1988;Okello, 2014; 12 cm 2 in Ceriops australis: Saenger and West, 2016). In general, the leaf area of Rhizophoraceae decreases along the order Rhizophora > Bruguiera > Kandelia > Ceriops.…”
Section: Leaf Area and Mass Per Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Griffin (1994) summarized a number of studies of leaf construction costs that found light and water availability affecting them. Saenger and West (2016) found leaf construction costs in a number of species of Australian mangroves tending to be higher the more complex their anatomical structure. Niinemets (1999a) found increased construction costs with increases of leaf mass area due to increased water stress higher in the canopy of temperate hardwood forests in Estonia.…”
Section: Construction and Maintenance Respiration Of Increasingly Commentioning
confidence: 96%